Noninvasive assessment of portal hypertension in patients with alcoholic cirrhosis - Tamara ALEMPIJEVI,; Aleksandra SOKIC-MILUTINOVIC,; Biljana MILICIC,; Rada JESIC,; Ana BALOVIC,; Dragan POPOVIC,; Miodrag KRSTIC, (Turkish Journal of Gastroenterology, 2019)
-